E-ViVa, the national Hellenic fulltext database on Librarianship and Information Science. Issue 4 (27th August 2014) - Tsimpoglou, Filippos; V. Koukounidou, Vasiliki; K. Sakka, Eleni
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to present E-ViVa (Ellinike Vivliothikonomike Vase), the national Hellenic fulltext database on Librarianship and Information Science, developed by the Library of the University of Cyprus. The objectives of E-ViVa are to identify, locate, gather, organize, index, digitize, preserve and promote the results of the research conducted in Greece and Cyprus in the scientific fields of Archival, Library and Information Sciences. Design/methodology/approach – The paper provides data concerning the volume, the coverage, the inclusion criteria, the content, the format and the platform of the database, as well as the steps that have been followed for the development. The legal framework related with the copyright issues that are raised are also discussed. Findings – A comparison is attempted between the coverage of E-ViVa and the relative records included in five subject-related databases: eLIS, LISA, LISTA, ISI-SSCI and SCOPUS. Finally the future plans for the project are presented. Research limitations/implications – Future plans concerning E-ViVa are based on the completeness of the database, the linguistic exploitation of the terms used through time and check of Lotka's law application concerning authors. Practical implications – As the vast majority of the records and fulltext are not provided by any other organized database, E-ViVa emerges as a "must search first" for any future author of scientific paper concerning the situation on librarianship research in Greece and Cyprus. The case of E-ViVa and the methodology that was followed can be used as a pattern for developing national databases on LIS or other fields. Social implications – E-ViVa is offered as an open access database with fulltext. Originality/value – E-ViVa is the only fulltext database on Librarianship and Information Science, which concentrates the related publications produced in or related to Greece and Cyprus.